THE EQUILIBRATION OF HIGH-ANGLE GRAIN BOUNDARIES IN DYNAMICALLY RECRYSTALLIZED QUARTZ: THE EFFECT OF CRYSTALLOGRAPHY AND TEMPERATURE - Kruhl J.H.; Peternell M. (My University, 2002)
Dynamically recrystallized and sutured quartz grains from metamorphic rocks with different strain intensities and temperature conditions ranging from ca. 350°C to ca. 700°C have been studied. Universal-stage measurements on quartz-quartz high-angle grain boundaries show that they are never curved but always consist of straight segments which preferentially occupy specific crystallographic orientations in relation to both neighboring crystals. With increasing temperature the segments preferentially concentrate in a decreasing number of orientations, mainly near the rhombohedral {1011} planes. The crystallographic data and the observations on grain boundary geometries suggest that: (i) grain boundary orientations are strongly crystallographically controlled, (ii) this control is the main factor on the textural equilibration of quartz-quartz grain boundaries in metamorphic rocks, and (iii) grain boundaries from dynamically recrystallized quartz should be regarded as annealed and equilibrated fabrics that are stable against subsequent annealing as long as the material is not re-deformed.
Keywords: RECRYSTALLIZED QUARTZ; CRYSTALLOGRAPHIC ORIENTATION; HIGH-ANGLE GRAIN BOUNDARIES; TEXTURAL EQUILIBRIUM